Testicular Niche Required for Human Spermatogonial Stem Cell Expansion. (18th July 2014) - Smith, James F.; Yango, Pamela; Altman, Eran; Choudhry, Shweta; Poelzl, Andrea; Zamah, Alberuni M.; Rosen, Mitchell; Klatsky, Peter C.; Tran, Nam D.
Abstract : This study characterizes the cellular niche required for the expansion of human spermatogonial stem cells (SSCs), provides strong evidence supporting specific extracellular markers that define a testicular cell population highly enriched for human SSCs, and characterizes a novel testicular multipotent stromal cell population essential for SSC expansion. The results of this study are very important to understanding how human SSCs can be grown and expanded successfully in vitro for future therapeutic applications. Abstract: : Prepubertal boys treated with high-dose chemotherapy do not have an established means of fertility preservation because no established in vitro technique exists to expand and mature purified spermatogonial stem cells (SSCs) to functional sperm in humans. In this study, we define and characterize the unique testicular cellular niche required for SSC expansion using testicular tissues from men with normal spermatogenesis. Highly purified SSCs and testicular somatic cells were isolated by fluorescence-activated cell sorting using SSEA-4 and THY1 as markers of SSCs and somatic cells. Cells were cultured on various established niches to assess their role in SSC expansion in a defined somatic cellular niche. Of all the niches examined, cells in the SSEA-4 population exclusively bound to adult testicular stromal cells, established colonies, and expanded. Further characterization of these testicular stromal cells revealed distinct mesenchymal markers and the ability to undergo differentiation along the mesenchymal lineage, supporting a testicular multipotent stromal cell origin. In vitro human SSC expansion requires a unique niche provided exclusively by testicular multipotent stromal cells with mesenchymal properties. These findings provide an important foundation for developing methods of inducing SSC growth and maturation in prepubertal testicular tissue, essential to enabling fertility preservation for these boys.